Effect of fluoride-containing desensitizing agents on the bond strength of resin-based cements to dentin - Duygu Saraç; Safak Külünk; Y. Sinasi Saraç; Özlem Karakas (University of São Paulo, 2009)
OBJECTIVE: The objective of this study was to evaluate the effect of desensitizing agents containing different amounts of fluoride on the shear bond strength of a dual polymerized resin cement and a resin-modified glass ionomer cement (RMGIC) to dentin. MATERIAL AND METHODS: One hundred human molars were mounted in acrylic resin blocks and prepared until the dentin surface was exposed. The specimens were treated with one of four desensitizing agents: Bifluorid 12, Fluoridin, Thermoline and PrepEze. The remaining 20 specimens served as untreated controls. All groups were further divided into 2 subgroups in which a dual polymerized resin cement (Bifix QM) or a resin-modified glass ionomer cement (AVANTO) was used. The shear bond strength (MPa) was measured using a universal testing machine at a 0.5 mm/min crosshead speed. The data were analyzed statistically with a 2-way ANOVA, Tukey HSD test and regression analysis (α=0.05). The effect of the desensitizing agents on the dentin surface was examined by scanning electron microscopy. RESULTS: The fluoride-containing desensitizing agents affected the bond strength of the resin-based cements to dentin (p<0.001). PrepEze showed the highest bond strength values in all groups (p<0.001). CONCLUSION: Regression analysis showed a reverse relation between bond strength values of resin cements to dentin and the amount of fluoride in the desensitizing agent (p<0.05).